Psychometric Analysis and Coupling of Emotions Between State Bulletins and Twitter in India During COVID-19 Infodemic - Aggrawal, Palash; Jolly, Baani Leen Kaur; Gulati, Amogh; Sethi, Amarjit; Kumaraguru, Ponnurangam; Sethi, Tavpritesh (Frontiers in Communication, 2021)
COVID19 infodemic has been spreading faster than the pandemic itself. The misinformation riding upon the infodemic wave poses a major threat to people’s health and governance systems. Managing this infodemic not only requires mitigating misinformation but also an early understanding of underlying psychological patterns. In this study, we present a novel epidemic response management strategy. We analyze the psychometric impact and coupling of COVID19 infodemic with official COVID19 bulletins at the national and state level in India. We looked at them from a psycho-linguistic lens of emotions and quantified the extent and coupling between them. We modified Empath, a deep skipgram-based lexicon builder, for effective capture of health-related emotions. Using this, we analysed the lead-lag relationships between the time-evolution of these emotions in social media and official bulletins using Granger’s causality. It showed that state bulletins led the social media for some emotions such as Medical Emergency. In contrast, social media led the government bulletins for some topics such as Hygiene, Government, Fun, Leisure. Further insights potentially relevant for policymakers and communicators engaged in mitigating misinformation are also discussed. We also introduce CoronaIndiaDataset, the first social-media-based Indian COVID19 dataset at national and state levels with over 5.6 million national and 2.6 million state-level tweets for the first wave of COVID19 in India and 1.2 million national tweets for the second wave of COVID19 in India.